2004
DOI: 10.1128/jvi.78.24.13460-13469.2004
|View full text |Cite
|
Sign up to set email alerts
|

Lytic Cycle Gene Regulation of Epstein-Barr Virus

Abstract: Episomal reporter plasmids containing the Epstein-Barr virus (EBV) oriP sequence stably transfected into Akata Burkitt's lymphoma cells were used to analyze EBV lytic cycle gene regulation. First, we found that the Zp promoter of EBV, but not the Rp promoter, can be activated in the absence of protein synthesis in these oriP plasmids, casting doubt on the immediate early status of Rp. An additional level of regulation of Zp was implied by analysis of a mutation of the ZV element. Second, our analysis of late l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 30 publications
(41 reference statements)
4
48
0
Order By: Relevance
“…This dependence on viral DNA synthesis has been linked to the origin of lytic replication (oriLyt), since the oriLyt sequence is required in cis for proper expression of late transcripts in many herpesviruses (42)(43)(44)(45)(46). However, our previous data and the data presented here demonstrate that viral gene expression at late times of infection depends not only on viral DNA in cis but also on viral factors such as pM92 and pM79 in trans (13).…”
Section: Discussionmentioning
confidence: 99%
“…This dependence on viral DNA synthesis has been linked to the origin of lytic replication (oriLyt), since the oriLyt sequence is required in cis for proper expression of late transcripts in many herpesviruses (42)(43)(44)(45)(46). However, our previous data and the data presented here demonstrate that viral gene expression at late times of infection depends not only on viral DNA in cis but also on viral factors such as pM92 and pM79 in trans (13).…”
Section: Discussionmentioning
confidence: 99%
“…Promoter regions (600 to 1,000 bp upstream of the translation initiation codon) of genes ORF57 (early or ␤), M3 (early-late or ␥ 1 ), ORF26 (true-late or ␥ 2 ), and ORF65 (true-late or ␥ 2 ) were cloned upstream of the firefly luciferase coding gene. It was reported that the late promoters of herpesviruses require a functional viral origin of lytic replication (oriLyt) in cis besides viral transfactors for activity (3,24). Hence, the late promoters were cloned into a vector containing the MHV-68 minimum oriLyt (13).…”
Section: Vol 80 2006 Orf18 Controls Gammaherpesvirus Late Gene Exprmentioning
confidence: 99%
“…Although the regulation of gammaherpesvirus IE and early gene expression has been studied extensively in tumor cell lines (8,22,49,56), studies on the regulation of late gene expression have been limited by the lack of a robust lytic system. EBV late lytic gene promoter sequences essential for the regulation of late gene expression have been mapped using a plasmid containing a late promoter-reporter and origin of lytic replication (3,43). Nevertheless, the viral factor(s) specifically controlling the transcriptional regulation of gammaherpesvirus late genes is unknown.…”
Section: Human Gammaherpesviruses Epstein-barr Virus (Ebv) Andmentioning
confidence: 99%
“…A hierarchy of viral gene expression is recognized in which the lytic transactivator ZTA (also called ZEBRA, Z, BZLF1, and EB1) is the first viral protein expressed, followed by the transcriptional and posttranscriptional regulatory proteins RTA (R) and MTA (SM) and subsequently the complement of EBV early and late genes (2,3,20). The key role of ZTA in the lytic reactivation process has resulted in an extensive examination of the regulation of the promoter that drives the BZLF1 open reading frame encoding ZTA.…”
mentioning
confidence: 99%